The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4315/0362-028x.jfp-14-190
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Compositions of Microflora of Vacuum-Packaged Beef Primal Cuts of Very Long Storage Life

Abstract: Vacuum-packaged top butt cuts from a beef packing plant that does not use any carcass decontaminating interventions were assessed for their organoleptic and microbiological properties during storage at 2 or -1.5°C. Cuts stored at 2°C were acceptable after storage for 140 days but were unacceptable after 160 days because of persistent sour, acid odors. Odors of cuts stored at -1.5°C for 160 days were acceptable. The numbers of aerobes on cuts increased from <1 log CFU/cm(2) to 7 or 6 log CFU/cm(2) for cuts stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Carnobacterium are also LAB and importantly have the capability of growing in temperatures as low as -1.5°C (Jones, 2004). Carnobacterium have been isolated from a number of different food sources, including pork, beef, poultry, cheese and seafood (Mauguin and Novel, 1994; Barakat et al, 2000; Cailliez-Grimal et al, 2005; Afzal et al, 2012; Rieder et al, 2012; Youssef et al, 2014). The genus produces a number of secondary metabolites with some of these (specifically class IIa bacteriocins) involved in the inhibition of the detrimental and pathogenic bacteria Listeria monocytogenes (Suzuki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Carnobacterium are also LAB and importantly have the capability of growing in temperatures as low as -1.5°C (Jones, 2004). Carnobacterium have been isolated from a number of different food sources, including pork, beef, poultry, cheese and seafood (Mauguin and Novel, 1994; Barakat et al, 2000; Cailliez-Grimal et al, 2005; Afzal et al, 2012; Rieder et al, 2012; Youssef et al, 2014). The genus produces a number of secondary metabolites with some of these (specifically class IIa bacteriocins) involved in the inhibition of the detrimental and pathogenic bacteria Listeria monocytogenes (Suzuki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature at which primals are stored and transported is between 1 to 2°C (Gill, Jones, Rahn, et al, 2002). The initially diverse microbial community on chilled vacuum packaged beef will be invariably replaced by a few species of LAB, which have growth advantage over other members of the meat microbiota at chiller temperatures under anaerobic condition provided by vacuum packaging (Holzapfel, 1998;Stanbridge & Davies, 1998;Youssef, Gill, Tran, & Yang, 2014;. Spoilage usually occurs only some time after the microbiota has reached maximum numbers as LAB are generally of low spoilage potential, due to the by-products of their metabolism being not highly offensive (Blixt & Borch, 2002;Castellano, Gonzá lez, Carduza, & Vignolo, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor contributing to the controversial role of carnobacteria is that the by-products generated by carnobacteria when growing on meat are not only species dependent, but also strain dependent (1,2,23). The inter-and intraspecies differences found in this study in bacteriocin and organic acid production provide insight into mechanisms by which certain strains of C. maltaromaticum extend the storage life of VP meat (28,30).…”
Section: Discussionmentioning
confidence: 75%
“…A few recent reports have demonstrated that Carnobacterium spp., particularly C. maltaromaticum, are associated with extremely long storage life of VP beef (27)(28)(29). However, the exact mechanisms by which they contribute to shelf life are not well understood, as information on the production of either bacteriocins or organic acids by and the antibacterial activities of these strains/species under VP meat-relevant anaerobic conditions is largely unavailable.…”
mentioning
confidence: 99%